INTENSIFICATION OF YEAST BIOMASS CULTURING IN A FILM BIOREACTOR - Voinov N.; Zhukova O.; Nikolaev A. (Foods and Raw Materials, 2013)
The results of Doctor N.A. Voinov and his colleaguesвЂ™ research aimed at developing gas-liquid film bioreactors are systematized. Fluid dynamics and heat and mass transfer in a liquid film flowing by gravity down a surface with artificial large-scale roughness have been investigated. Relationships based on the plug flow model are suggested for calculating mass transfer in the working zones of the bioreactor. Ways of raising the productivity of the apparatus and reducing the cost of culturing Candida scottii yeast are considered. Closed-loop gas circuit schemes are suggested for the film bioreactor.